Development and assessment of a data collection method for route choice in public transport - Anderson, Marie K. A. (Proceedings from the Annual Transport Conference at Aalborg University, 2010)
Knowledge about actual route choices for public transport passengers is important when assessing generated choice sets for route choice modelling. An objective measure of relevant routes in actual networks does not exist and assessment of the choice sets is often based on the experience and knowledge of the analyst. Route choices for car traffic have attracted a lot of attention in the research literature, but limited knowledge exists on the route choices of public transport passengers and the need for insight into these choices motivates the work described in the paper. This paper describes a method to collect data for public transport passengers by using internet and telephone interviews. The route choice questions are formulated and added to the existing Danish Travel Survey (Transportvaneundersøgelsen, TU) and tested in a pilot study at the Technical University of Denmark (DTU). Afterwards, the questions are implemented in the national TU survey and, since February 2009, more than 4,000 route choices in public transportation have been collected. The method of collecting public route choices proves to be successful since it collects actual route choice data for a large number of travellers and it allows reproducing observed choices in a GIS network for choice set assessment purposes.